Scoping the Scene: What Do Nurses, Midwives, and Allied Health Professionals Need and Want to Know About Genomics? - Saleh, Mona; Kerr, Romy; Dunlop, Kate (Frontiers in Genetics, 2019)
Rapid changes in genomic technology are transforming healthcare delivery. Although it has been well established that many health professionals lack the adequate knowledge, skills and confidence to adapt to these changes, the specific educational needs of Australian allied health professionals, nurses and midwives are not well understood. This diverse group of health professionals are primarily involved in the management of symptoms and psychosocial care of patients with genetic conditions, rather than risk assessment and diagnosis. The relevance of genetics and genomics to their clinical practice may therefore differ from medical practitioners and specialists. This paper reports on a study undertaken to identify the perceived genetic knowledge and education needs for this group of health professionals. Allied health professionals, nurses and midwives were recruited from throughout NSW and invited to participate in semi-structured telephone or face to face interviews. A total of 24 geographically and professionally diverse individuals (14 Allied Health, 6 Nurses and 4 midwives) were interviewed. Interview recordings were transcribed and using thematic qualitative analysis recurring themes were identified. The results show that this is a diverse group that is keen to know more about genomics and genetic services but unsure of reliable sources. The need for a generic update from a trustworthy source was identified and suggested topics to be covered included genetic fundamentals, recognizing common genetic conditions and psychosocial/ethical aspects of genetics/testing including informed consent. In addition, the challenge of incorporating education in to highly clinical roles was identified as a key barrier and having a readily accessible, accredited learning resource would help overcome this. Findings from this study are informing the development of a targeted, interactive e-learning resource for allied health professionals, nurses and midwives.